Determining efficient delivery routes in specific time-frames using Geographic Information System - Abousaeidi, M.; Fauzi, R.; Muhamad, R. (Triveni Enterprises, 2016)
Perishable products must be transported quickly from its production area to the markets due to the climatic conditions of Malaysia. Deterioration of fresh produce is affected by temperature and delivery time. The cost to achieve such timely delivery of perishable food can affect the revenue of suppliers and retailers. Choosing an efficient delivery route at right time can reduce the total transportation cost. However, insufficient attention has been given to transportation issues with regards to fresh food delivery of greater Kuala Lumpur. The present study involves adoption of the Geographic Information System (GIS) modelling approach to determine the fastest delivery routes for fresh products to several hypermarkets. For this purpose, ArcGIS software was adopted for solving the problem of a complex road networks. With a goal of realizing the shortest time for delivery route planning, impedance function would be integrated by taking into account the time emphasized in the study. The main findings of this study include determination of efficient routes for delivery of fresh vegetables based on minimal drive time. It has been proposed that the fastest route model for delivery of fresh products is based on comparing two time frames within a day. The final output of this research was a map of quickest routes with best delivery time based on two time frames.